Kabupaten Tebo Provinsi Jambi Tahun 1999-2010 Suatu Tinjauan Sejarah Pemekaran Kabupaten - Astuti, Rina - (Pendidikan Sejarah, 2014)
Â This thesis examined about the developing of the district of Tebo Jambi from the beginning. The district of Tebo which officially separated from district of Bungo in 1999 by publication of UU No 54 year 1999 about the form of district of Tebo and three other districts in Jambi. Besides, it W<f> also see the potential of Tebo and the development of Tebo after developing it into a district in social, culture and economics field that is three important fields to get social prosperity <f> the honorable goal of this developing. B<fled on the main problem above, the problems of the research are (a) what is the background problem of developing the district of Tebo in 1999 (b) how was the development of Tebo after developing in social, culture and economical field during 1999-2000. This research used historical method involving heuristic, source critics, analysis, synthesis, interpretation and historiography (the historical writing). First, the writer collected the data relating to research object by using two kinds of data namely primary data and secondary data The primary data is gotten by interviewing with sources and other sources, but the secondary data is gotten by library research. Second, it was done source critics to the data Third, analyze, synthesize, and interpret the data Fourth, the writer showed the research result in a form of thesis. The research result showed that the district ofhTebo is developed from Bungo on October 41 1999, so there was a movement in social, culture andeconomics field because the government started to focus on public prosperity. The developing of Tebo gave more effects toward Tebo society than other district society before the developing of Tebo. The social interaction act gave positive effects. In economics field, the society of Tebo had more progress. It could be seen from peoples houses and the roads. Furthermore, the district of Tebo is also rich of natural sources such as coal and petroleum.